Patenting strategies in the German mechanical engineering industry and their relationship to company performance - Ernst, H.
Fifty German mechanical engineering firms were studied with regard to their patenting behaviour. Four different patenting strategies were identified and the relationship between such strategies and company performances was evaluated.
This paper systematically evaluates the patenting behaviour of a sample of 50 business firms within the German mechanical engineering industry. Based on a framework of multiple patenting indicators, four different types of patenting strategies are identified. Furthermore, the relationship between these patenting strategies and company performance is analysed. It is shown that patent-active companies perform best for the economic performance variables used. Finally, the importance of different patenting indicators is assessed. It is found that the number of international patent applications, the rate of valid patents and highly cited patents are positively related to economic performance. Thus, a differentiated use of patent data is advisable.
Keywords: Patenting strategies; Mechanical engineering industry--Germany.; Company performance